Efektivitas Intervensi Ergonomi terhadap Work-Related Musculoskeletal Disorders pada Pekerja Pertanian: Literature Review - Ahmad Eko Wibowo; Candra Dermawan; Risky Kusumawardani; Hanan Alawiyah; Baiq Deisy Pupiyati; Iman Firmansyah; Nurfika Asmaningrum (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2026)
Background: Work-related musculoskeletal disorders (WMSDs) are a major occupational health concern among agricultural workers worldwide, with a prevalence up to 50% higher than that of workers in non-agricultural sectors, due to exposure to repetitive and prolonged non-ergonomic working postures. However, guidelines for implementing evidence-based ergonomic interventions that can be carried out by community nurses in Indonesia remain limited. Objective: To review the effectiveness of ergonomic interventions in reducing WMSDs risk and complaints among agricultural workers in community settings based on recent evidence (2020–2025). Method: A systematic literature search was conducted across four databases (Scopus, PubMed, Cochrane/Wiley, Google Scholar). From 135 identified articles, 93 unique articles were obtained after deduplication; 12 final articles were included after screening and eligibility assessment. JBI critical appraisal tools were applied. Result: Twelve articles encompassed cross-sectional, quasi-experimental, observational, and review designs. WMSDs prevalence ranged from 39–76%, with low back pain, shoulder pain, and neck pain as the most common complaints. Ergonomic interventions including posture training, tool redesign, and participatory ergonomics significantly reduced musculoskeletal complaints. Conclusion: Ergonomic interventions are effective in reducing WMSDs among agricultural workers. Community nurses play a strategic role in implementing evidence-based ergonomic programs.INTISARILatar belakang: Gangguan muskuloskeletal terkait pekerjaan (WMSDs) merupakan masalah kesehatan kerja utama pada pekerja pertanian di seluruh dunia, dengan prevalensi mencapai 50% lebih tinggi dibandingkan pekerja di sektor non-pertanian akibat paparan postur kerja nonergonomis berulang dan berkepanjangan. Namun panduan implementasi intervensi ergonomi berbasis bukti yang dapat dilakukan perawat komunitas di Indonesia masih terbatas. Tujuan: Menelaah efektivitas intervensi ergonomi dalam menurunkan risiko dan keluhan WMSDs pada pekerja pertanian di setting komunitas berdasarkan bukti ilmiah terkini (2020–2025). Metode: Penelusuran sistematis dilakukan pada empat database (Scopus, PubMed, Cochrane/Wiley, Google Scholar). Dari 135 artikel teridentifikasi, 93 unik setelah deduplikasi, dan 12 artikel final diinklusi setelah skrining dan asesmen eligibilitas. Penilaian kualitas menggunakan instrumen JBI. Hasil: Dua belas artikel mencakup desain cross-sectional, quasi-experimental, observasional, dan review. Prevalensi WMSDs berkisar 39–76%, dengan low back pain, nyeri bahu, dan nyeri leher sebagai keluhan terbanyak. Intervensi ergonomi pelatihan postur, redesain alat, dan participatory ergonomics terbukti signifikan menurunkan keluhan muskuloskeletal. Simpulan: Intervensi ergonomi efektif menurunkan WMSDs pada pekerja pertanian. Perawat komunitas berperan strategis dalam implementasi program ergonomi berbasis bukti.